Impact of Organic Nutrient Management on Growth, Fruiting and Yield of Avocado (Persea americana) under Hilly Region of West Bengal - Subba, Saidiksha; Gurung, Sarad; Bhowmick, Nilesh; Devi, M. P.; Mandal, Somnath; Ghosh, Arunava; Chhetri, Binoy (International Journal of Economic Plants, 2026)
An experiment was laid out in farmer’s field of Kamjer village, Kalimpong during the month (March to August) of the year 2022–2023 at farmer’s field in Kamjer village, Kalimpong, West Bengal to study the effect of organic sources of nutrients on growth, yield and quality of avocado with eight different treatments (T1) FYM (40 kg plant-1), (T2) Vermicompost (20 kg plant-1), (T3) Leaf mould (20 kg plant-1), (T4) Mustard cake (15 kg plant-1), (T5) Poultry manure (15 kg plant-1), (T6) Pig manure (10 kg plant-1), (T7) Goat manure (10 kg plant-1) and (T8) RDF NPK (500 g, 250 g and 450 g plant-1) having three replication in Randomized Block Design (RBD). Result indicated that avocado trees treated with 20 kg vermicompost tree-1 (T2) gave the best result with respect to maximum plant height (9.53 and 10.88 m), span canopy volume (159.16 and 216.07 m3), trunk girth (55.79 and 56.97 cm), maximum number of flowers shoot-1 (73.25 and 80.91), maximum percentage fruit set (46.65 and 48.52%), maximum fruit retention percentage (27.82 and 29.01%), maximum specific gravity (1.16 and 1.30), fruit diameter (6.98 and 6.49 cm), fruit length (9.88 and 9.98 cm), highest seed weight (45.56 and 52.37 g), maximum number of fruits shoot-1 (34.18 and 39.25), maximum number of fruits tree-1 (236.03 and 242.11), maximum fruit weight (330.27 and 343.93 g) and highest yield (77.98 and 83.26 kg tree-1 ) as compared to other treatments.